Benefícios obtidos na colaboração entre sistemas MES e sistemas de manufatura digital do PLM - Diagnóstico - Gama, Evandro Bertoni da (2011)
A necessary condition for the economic efficiency of modern plants is the ability to adjust - as quickly and effectively as possible - the performance of manufacturing process for demand request decisions. In this sense, the research emphasized the importance of understanding the best practices in Information Technology (IT) and the trade scenario of solutions using shopfloor real data in virtual environments for simulation and many achieved benefits. The highlights of this research focused on exploring the collaboration (practice of skills for the achievement of mutually beneficial results) between the MES (Manufacturing Execution Systems) and the digital manufacturing systems (also called virtual manufacturing systems) of PLM (Product Lifecycle Management), in a scenario where the manufacturing processes require high flexibility, reliability and lower delivery times, extensive combination of variants and lower life-cycle of products. The research - in an exploratory and descriptive way, which identified the available knowledge on the subject more sharply between the years 2006 and 2010 - was grounded in the practices of world-renowned companies and institutions and considered opinions and evaluations of renowned researchers and professionals with expertise in initiatives to support the use of MES solutions data in systems of digital manufacturing of PLM to manufacturing processes planning. As a result of the studied scenarios and covered concepts, the research has consolidated a "diagram of information collaboration", with the aim of providing better decision choices within the framework of shop-floor project, processes planning and production management. The research also concluded that the MES systems may have their value extended if integrated within the characteristics of functionalities of the PLM concept. It also brought some recommendations and limitations on the portability of information, commented on the learned lessons and suggestions for future tasks that include the BPM (Business Process Management).